Extreme teaming : lessons in complex, cross-sector leadership - Edmondson, Amy C.; Harvey, Jean-François (Emerald Publishing Limited, 2017)
Today's global enterprises increasingly involve collaborative work by teams of experts operating across different professions, organizations, and industries. Extreme Teaming provides new insights into the world of complex, cross industry projects and the ways they must be managed. Leading experts Amy Edmondson and Jean-François Harvey analyze contemporary cases that expose the complex demands of cross-boundary collaboration on management, and inform our understanding of teams. Containing powerful insights and practical guidelines that allow managers to bridge professional divides and organizational boundaries in order to work together effectively, this is a new exploration of the challenges involved in today's global enterprises. The authors demonstrate that the work done in the modern organization is less and less about looking inward and creating strong teams inside the company, and more about teaming across boundaries - that often are in flux. Extreme Teaming is a must-read book for all courses related to leading open innovation; teamwork and collaboration; project management; and cross-boundary work.